(untitled) (Indian Journal of Public Health Research & Development, 2025)
Dentists are exposed to various types of chemicals while providing care that are hazardous. There are many potentially toxic materials that are used in dentistry that can pose a serious health hazard in the absence of appropriate precautionary measures. These include hazardous chemical agents used in clinical dentistry including Mercury, powdered natural rubber latex (NRL), disinfectants, methyl methacrylate, metal alloys, silica, and nitrous oxide (N2O). Exposure to these chemicals can result in acute and chronic health effects. Acute effects include skin and eye irritation, respiratory distress, and allergic reactions, while chronic exposure can lead to more serious conditions such as asthma, neurological disorders, and even cancer. This review article aims to identify and categorize the common chemicals used in dental practices and their associated health hazards and to provide safety guidelines and best practices for minimizing exposure to hazardous chemicals in dental settings.